The Effect of Using Kagan's Structure in Knowledge Achievement and Self-esteem in the Kurdish Literature by Eighth-Grade Basic Students - Srwa Alaaddin Omer; Chiman Hamza Drwish (Zanco Journal of Humanity Sciences)
The aim of this study is to find out the effect of using Kagan's structure in knowledge achievement and self-esteem in the Kurdish literature by the eighth-grade basic students.